Quality of life of family caregivers of children with microcephaly - Layla Beatriz Melo de Oliveira; Aline Costa de Oliveira; Daniel de Macêdo Rocha; Márcia Teles de Oliveira Gouveia; Rosana dos Santos Costa; Lídya Tolstenko Nogueira (Acta Scientiarum. Health Sciences, 2021)
Assess the quality of life of family caregivers of children with microcephaly. This is an analytical cross-sectional study developed in Teresina-PI, carried out in a rehabilitation center. For data collection a form was used to investigate the sociodemographic profile and the Medical Outcomes Study 36 - Item Short-Form Health Survey instrument to assess quality of life. For data analysis, we used the statistical tests Student's t, ANOVA, U- Mann Whitney and Kruskal-Wallis. The descriptive analysis of the results showed that the functional capacity domain presented the most impairment by obtaining the highest score. The dimensions vitality and pain showed the lowest averages, representing the less affected domains. The associations between the sociodemographic characteristics and the domains of quality of life were significant between the variables marital status and pain, education and the domains vitality and emotional aspect, and between employment status and general health status. The quality of life of family caregivers presented losses related to the change of routine and the difficulties faced on a daily basis, highlighting the importance of covering the health of caregivers within the assistance offered to children with special needs, contributing to the well-being of those who care and consequently of those who are cared for.